Validating five questions of antiretroviral nonadherence in a public-sector treatment program in rural South Africa - Chaiyachati, Krisda; Tanser, Frank; Newell, Marie-Louise; Bärnighausen, Till (AIDS patient care and STDs, 2011)
Simple questions are the most commonly used measures of antiretroviral treatment (ART) adherence in sub-Saharan Africa (SSA), but rarely validated. We administered five adherence questions in a public-sector primary care clinic in rural South Africa: 7-day recall of missed doses, 7-day recall of late doses, a six-level Likert item, a 30-day visual analogue scale of the proportion of doses missed, and recall of the time when an ART dose was last missed. We estimated question sensitivity and specificity in detecting immunologic (or virologic) failure assessed within 45 days of the adherence question date. Of 165 individuals, 7% had immunologic failure; 137 individuals had viral loads with 9% failure detected. The Likert item performed best for immunologic failure with sensitivity/specificity of 100%/5% (when defining nonadherence as self-reported adherence less than 'excellent'), 42%/55% (less than 'very good'), and 25%/95% (less than 'good'). The remaining questions had sensitivities ≤17%, even when the least strict cutoffs defined nonadherence. When we stratified the analysis by gender, age, or education, question performance was not substantially better in any of the subsamples in comparison to the total sample. Five commonly used adherence questions performed poorly in identifying patients with treatment failure in a public-sector ART program in SSA. Valid adherence measurement instruments are urgently required to identify patients needing treatment support and those most at risk of treatment failure. Available estimates of ART adherence in SSA are mostly based on studies using adherence questions. It is thus unlikely that our understanding of ART adherence in the region is correct.
Gesehen am 19.09.2011